KEPUASAN PELANGGAN INTERNAL - Rosni Faika; O Sianipar (Indonesian Association of Clinical Pathologist and Medical laboratory, 2007)
Customer satisfaction survey is one of efforts of continuously quality improvement of care and also can be used to maintain customers that already utilize available services. Efforts of corrective action should be done based on result of this survey. The objective of this surveyis to assess desired-service and reality of the service undergone by internal customer and to improve quality of service of laboratorymedicine in Clinical Laboratory of Dr. Sardjito Hospital, Yogyakarta. This is cross sectional customer satisfaction survey. Subject of thissurvey are 23 doctors work in Dr Sardjito Hospital. Data collected by questionnaire that contain 18 items about desired-service andreality of service undergone by internal customer from service given by Clinical Laboratory of Dr. Sardjito Hospital. Respondents assessdesired-service and reality of service using Likert scale. The obtained data are analyzed by Cartesius diagram. Result of the survey showsthat average concordant between desired-service and reality of service is 85.5%. Main priority corrective action to improve quality ofservice are: 1) readiness of registry staff; 2) easiness of registration procedure; 3) skill of laboratory staff in explaining and recordingtest parameter; 4) service of cito service; 5) 24 hours laboratory service and 6) timely laboratory test.